Specifying High Altitude Electrons Using Low‐Altitude LEO Systems: Updates to the SHELLS Model - A. J. Boyd; J. C. Green; T. P. O’Brien; S. G. Claudepierre (Space Weather)
Abstract We describe a new version of the SHELLS model, which specifies the outer electron belt environment as observed by the Van Allen Probes using the Kp Index and data from Polar‐orbiting Operational Environmental Satellites and the Meteorological Operational satellites as inputs. The updated model combines the radial, angular and energy dependence into a single neural network, allowing for specification of the electron environment for a set of user input energy, L‐shell and Bmirror values. We demonstrate that the model can accurately reproduce the outer electron radiation belt dynamics using both out‐of‐sample data from the Van Allen Probes and measurements from the Combined X‐ray Dosimeter instrument on GPS. This updated model will provide valuable characterization of the internal charging hazard for non‐GEO orbits, particularly in the post‐Van Allen Probes era.